Pendekatan Ekonomi Sirkular sebagai Model Pengembangan Bisnis melalui Pemanfaatan Aplikasi pada Usaha Kecil dan Menengah Pasca Covid-19 - Muhammad Haris Fadhillah; Mohammad Fahreza (Coopetition : Jurnal Ilmiah Manajemen, 2023)
Some research about economic restoration after covid-19 have been researched, but nothing is focused on discussing circular economy (CE). Circular economy is an alternative to reduce waste and fix the environment. CE maximizing benefit between economic and environment. This research is implemented by the CE approach of Ellen Macarthur Foundation, there is reduce, reuse, recycle, refurbish, and renew. The results of this research show that SME in Kabupaten Sumedang have enormous potential in improving their standard of living which combines economic and environment. As it supports a circular economy, the application based on technology is very helpful in the process of its implementation.